Overt and Subclinical Hypothyroidism in the Elderly: When to Treat? - Calsolaro, Valeria; Niccolai, Filippo; Pasqualetti, Giuseppe; Calabrese, Alessia Maria; Polini, Antonio; Okoye, Chukwuma; Magno, Silvia; Caraccio, Nadia; Monzani, Fabio (Frontiers in Endocrinology, 2019)
Hypothyroidism is characterized by increased thyrotropin (TSH) levels and reduced free thyroid hormone fractions while, subclinical hypothyroidism (sHT) by elevated serum TSH in the face of normal thyroid hormones. The high frequency of hypothyroidism among the general population in Western Countries made levothyroxine (LT4) one of the 10 most prescribed drugs. However, circulating TSH has been demonstrated to increase with ageing, regardless the existence of an actual thyroid disease. Thus, when confronting an increase in circulating TSH levels in the elderly, especially in the oldest old, it is important to carry an appropriate diagnostic path, comprehensive of clinical picture as well as laboratory and imaging techniques. In the current review, we summarize the recommendations for a correct diagnostic workup and therapeutic approach to older people with elevated TSH value, with special attention to the presence of frailty, comorbidities and poly-therapy. The treatment of choice for hypothyroid patients is hormone replacement with LT4 but, it is important to consider multiple factors before commencing the therapy, from the age dependent TSH increase to the presence of an actual thyroid disease and comorbidities. When treatment is necessary, a tailored therapy should be chosen, considering poly-pharmacy and frailty. A careful follow-up and treatment re-assessment should be always considered to avoid the risk of over-treatment. It is important to stress the need of educating the patient for a correct administration of LT4, particularly when poly-therapy is in place, and the importance of a tailored therapeutic approach and follow-up, to avoid overtreatment.